HUBUNGAN FAKTOR RESIKO DENGAN KEJADIAN PADA PENYAKIT PARU OBSTRUKSI KRONIK DI PUSKESMAS MANDALA - Alamsyah Lukito (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2019)
The main cause of Chronic Obstructive Pulmonary Disease is smoking or exposure to secondhand smoke from active smokers or smoke inhalation in passive smokers. Other causes are air pollution, workplace exposure, and genetic factors. This type of research is analytical research with a cross sectional approach which aims to study the existence of a variable relationship dynamics. In this study, the sample was 30 patients from the Mandala Health Center. Generally, COPD sufferers are those aged 45 years to 65 years where 21 of the 30 people suffer from risk. The chi-square test results show that there is a relationship between risk factors and the incidence of COPD in the Tembung Mandala 2018 Health Center Working Area.